2017
DOI: 10.1186/s13071-017-2197-2
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation in murine macrophages caused by Neospora caninum infection

Abstract: Background Neospora caninum is an intracellular parasite that causes significant economic losses in cattle industry. Understanding the host resistance mechanisms in the innate immune response to neosporosis could facilitate the exploration of approaches for controlling N. caninum infection. The NLR inflammasome is a multiprotein platform in the cell cytoplasm and plays critical roles in the host response against microbes.Methods Neospora caninum-infected wild-type (WT) macrophages and Nlrp3 −/− macrophages, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…Our previous study showed that N. caninum could induce IL-1β release and caspase-1 activation in murine peritoneal macrophages ( 15 ). To determine if N. caninum also activates the inflammasome in BMDMs, unstimulated and LPS pre-treated BMDMs were infected with N. caninum (parasite:cell MOI = 1 or 3) for 3 h. BMDMs with culture medium alone did not produce measurable levels of IL-1β (p17) or active caspase-1 (p20).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study showed that N. caninum could induce IL-1β release and caspase-1 activation in murine peritoneal macrophages ( 15 ). To determine if N. caninum also activates the inflammasome in BMDMs, unstimulated and LPS pre-treated BMDMs were infected with N. caninum (parasite:cell MOI = 1 or 3) for 3 h. BMDMs with culture medium alone did not produce measurable levels of IL-1β (p17) or active caspase-1 (p20).…”
Section: Resultsmentioning
confidence: 99%
“…However, glyburide did not greatly impair the production of IL-6 (Figure 1 J). Our previous study has shown that glyburide could slightly inhibit the replication of N. caninum in Vero cells but not affect its abilities of invasion and viability ( 15 ). These data indicate that K + efflux participates in the signals that activate NLRP3 inflammasome in N. caninum -infected BMDMs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations